Characterization of thermal behavior of a micro pulsating heat pipe by local heat transfer investigation. (1st November 2022) - Iwata, Naoko; Bozzoli, Fabio; Pagliarini, Luca; Cattani, Luca; Vocale, Pamela; Malavasi, Matteo; Rainieri, Sara
Highlights: A 7-turn tubular pulsating heat pipe with an inner diameter of 0.32 mm was tested. Temperature distribution of condenser was measured by an infrared camera. Different flow regimes were shown depending on power input. Local heat flux was estimated by solving inverse heat conduction problem. Dominant oscillation frequency was found around 1.2 Hz at high power input. Abstract: The thermal behavior of Pulsating Heat Pipes (PHPs), which is inherently time-dependent, could also significantly change from local position to local position. Hence, the evaluation of local heat flux distributions could lead to a better understanding of the fundamental governing mechanisms of PHPs, which are, so far, only partially understood. In fact, most of the studies regarding the working principles of PHPs have focused on analysing the heat transfer rate averaged over the evaporator and condenser areas, or on evaluating the overall thermal resistance of the system. A 7-turn micro-PHP with an inner diameter of 0.32 mm was charged with HFC-134a at filling ratio of 46% and tested in bottom heated mode. The external wall temperature distribution of the condenser was measured by a high-speed and high-resolution infrared camera. The local heat fluxes exchanged between the fluid and the PHP wall were estimated in the whole condenser by solving the inverse heat conduction problem with the temperature maps as input data. In order to study the PHP working regimes, the local heat transfer behavior was furthermore investigated in terms of characteristic frequencies of the oscillatory flow by means of the wavelet method, coupled with a statistical approach. At low heat input the variations over time and along space of axial coordinate in the heat flux were significant and each tube showed multiple peaks in the power spectrum. On the other hand, the variation weakened under the high heat input conditions and the dominant fluid oscillation frequency was found more clearly around 1.2 Hz. All the qualitative and quantitative pieces of data are comprehensively presented to give further information regarding the device behavior at different heat input.